LAND, LITURGY & LIFE: OVERTURE TO THE ‘COMMA’ AND THE ‘AND’ IN A VERY SMALL DOGMATICS - Conradie, Ernst M. (Scriptura, 2013)
This contribution observes a Trinitarian logic in the theme of ‘Land, Liturgy and Life’ addressed at the 2013 annual meeting of the Theological Society of South Africa. The Trinitarian mystery needs to be protected with the doxological language of the liturgy. In this contribution I will offer an overture (or prolegomena) to such a doxology, by weaving together four themes pertaining to the nature of the Christian confession of faith in the triune God. In a rather unreformed move I will give a certain priority to seeing instead of hearing and suggest a) that the Christian con-fession offers a way of seeing the world, b) that it sees the world (the land) as the beloved household of God, c) that this is best understood as a liturgical vision and d) that it is this vision that enables the resurrection of life.